2016
DOI: 10.1002/ejoc.201600719
|View full text |Cite
|
Sign up to set email alerts
|

Stereoretentive H/D Exchange via an Electroactivated Heterogeneous Catalyst at sp3 C–H Sites Bearing Amines or Alcohols

Abstract: This report describes a mild, aqueous‐phase strategy that enables stereoretentive C–H activation at sp3 C–H sites bearing amine or alcohol groups. The transformation utilizes D2O to replace the hydrogen with deuterium while retaining stereochemistry. Electroactivated ruthenium particles, which are supported by an activated carbon cloth (Ru/ACC), catalyze this reaction on a timescale of minutes to hours. This yields optimal results at low current density and mild temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 74 publications
0
27
0
Order By: Relevance
“…12,13 Finally, D 2 is commonly employed as the deuterium source, which is more expensive than D 2 O and imposes additional operational challenges. 14 To overcome these limitations, we present a stereoretentive labeling protocol of primary amines that employs inexpensive D 2 O.…”
mentioning
confidence: 99%
“…12,13 Finally, D 2 is commonly employed as the deuterium source, which is more expensive than D 2 O and imposes additional operational challenges. 14 To overcome these limitations, we present a stereoretentive labeling protocol of primary amines that employs inexpensive D 2 O.…”
mentioning
confidence: 99%
“…[ 84 ] Recently, Jackson et al have reported the application of electroactivated ruthenium particles, which are supported by an activated carbon cloth (Ru/ACC), that enables stereoretentive C-H activation at sp 3 C-H sites bearing amine or alcohol groups. [85] Generally the applications of nanoparticles show different reactivity or selectivity compared to the already known homogeneous or heterogeneous HIE reaction systems. It is, therefore, anticipated that advances in material science will also enrich the armory of HIE reaction methods in the future.…”
Section: Hie Reactions With Nanoparticlesmentioning
confidence: 99%
“…Recently, Bhatia et al described an HIE reaction catalyzed by electro‐activated ruthenium particles on an activated carbon cloth (Ru/ACC) that enabled stereoretentive C–H activation at sp 3 C–H sites bearing amine or alcohol groups . Generally, nanoparticles, on the borderline between homogeneous and heterogeneous catalysts, show unique reactivities or selectivities compared with the already known catalysts applied in HIE reactions.…”
Section: Aliphatic C(sp3)‐h Hydrogen Isotope Exchange Reactionsmentioning
confidence: 99%